Analysis of Medicine Use in Disaster Management - Wulandari, Tri; Abriani, Nurul Gilang (Poltekkes Kemenkes Gorontalo, 2025)
Medicine is the basic logistics to meet the basic needs in disaster management. The use of medicine in disaster management is adjusted to the needs during a disaster. Different types of medicine on pharmacological effects determine the use of medicine in the disaster emergency category. This research is to analyze the use of medicine based on the types of markers and pharmacological effects needed in disaster management. Data collection used descriptive design and methods based on medicine use in the last five years of disaster management in Karanganyar district collected from medical records and interviews. Medicine was categorized based on the drug packaging labeling as general sales list, pharmacy medicines, prescription-only medicines, and controlled group medicine. Based on the effect of pharmacology, medicine can be used as vaccines, psychotropics, multivitamins, analgesics, antipyretics, antibiotics, antiviruses, corticosteroids, mucolytics, anthelmintics, gastritis, and flu. So it is concluded that based on the type of marker, there are three, and not all medicines that have a pharmacological effect are used in disaster management. The implication of this study is that medication requests should align with the needs of the specific type of disaster.